If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + -12) = (2x + -9) Reorder the terms: (-12 + 7x) = (2x + -9) Remove parenthesis around (-12 + 7x) -12 + 7x = (2x + -9) Reorder the terms: -12 + 7x = (-9 + 2x) Remove parenthesis around (-9 + 2x) -12 + 7x = -9 + 2x Solving -12 + 7x = -9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -12 + 7x + -2x = -9 + 2x + -2x Combine like terms: 7x + -2x = 5x -12 + 5x = -9 + 2x + -2x Combine like terms: 2x + -2x = 0 -12 + 5x = -9 + 0 -12 + 5x = -9 Add '12' to each side of the equation. -12 + 12 + 5x = -9 + 12 Combine like terms: -12 + 12 = 0 0 + 5x = -9 + 12 5x = -9 + 12 Combine like terms: -9 + 12 = 3 5x = 3 Divide each side by '5'. x = 0.6 Simplifying x = 0.6
| 9x+2=6x+23 | | -1(3x-4)+8=27 | | 2/5x=4/25 | | 9x+4+2x+2= | | 2^x(5^x)=1/100(10^x-1)^4 | | 2x^2-7x+20=0 | | 2r-4t+3t= | | (a+6)+2bi=6-i | | 0.99n=10+0.89n | | 4w+10=42 | | -5.1s=66.3 | | 15-2b-5=-9 | | 12.54+.12(x+3)=13.04-.14 | | 51=-3x^2-3 | | 10b+4(3b-2)= | | 2n+4+3=1 | | Log243n=4/5 | | 6x+5=-7+3x+18 | | 32z^2=18 | | 3x-[x-(4x+2y)+4y]-5= | | -3x-7=6(x+3) | | n/0 | | 10/8=x/20 | | a^2-a+10=10 | | 8-5x=x+8 | | 7+0.20n=5+0.30n | | ln(x+3)=ln(10)-ln(x) | | (8-4)8x-9y=4 | | 16+5x=4(3x+7) | | 4a-(3a-2b)+3a= | | 5x-45=3x-7 | | 100+80n=250+70n |